Nickel(II) N‐Heterocyclic Carbene Complexes: Versatile Catalysts for C–C, C–S and C–N Coupling Reactions. Issue 19 (18th May 2017) - Junquera, Lourdes Benítez; Fernández, Francys E.; Puerta, M. Carmen; Valerga, Pedro
Abstract : A variety of Ni II complexes with a wide range of electronic and steric properties, bearing picolylimidazolidene ligands (a –g ) and Cp (Cp = η 5 ‐C5 H5 ;2a –f ) or Cp* (Cp* = η 5 ‐C5 Me5 ;3a, c, g ) groups, have been synthesised and characterised by using NMR spectroscopy and single‐crystal X‐ray crystallography. The complexes have been used as precatalysts for a wide range of catalytic transformations, which most likely involve a Ni 0 /Ni II catalytic cycle. In particular, the new well‐defined2a, 2c, 3a and3c complexes have demonstrated great efficiency and versatility towards Suzuki–Miyaura coupling reactions, hydroamination of activated olefins and C–S cross‐coupling reactions of aryl halides and thiols under mild conditions. Abstract : Efficient and versatile Ni II N‐heterocyclic carbene (NHC) complexes for Suzuki–Miyaura coupling reactions, hydroamination of activated olefins and C–S cross‐coupling of aryl halides and thiols are reported.